2021
DOI: 10.3390/cells10081982
|View full text |Cite
|
Sign up to set email alerts
|

Does Schistosoma Mansoni Facilitate Carcinogenesis?

Abstract: Schistosomiasis is one of the most prominent parasite-induced infectious diseases, causing tremendous medical and socioeconomic problems. Current studies have reported on the spread of endemic regions and the fear of development of resistance against praziquantel, the only effective drug available. Among the Schistosoma species, only S. haematobium is classified as a Group 1 carcinogen (definitely cancerogenic to humans), causing squamous cell carcinoma of the bladder, whereas infection with S. mansoni is incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 146 publications
0
16
0
Order By: Relevance
“…It is important to note, however, that the available data regarding the precise role of S. mansoni in the process of carcinogenesis are conflicting and often lack conclusive evidence of causality. This underscores the need for further comprehensive research to elucidate the intricate relationship between this parasitic infection and the development of hepatic disorders ( 92 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note, however, that the available data regarding the precise role of S. mansoni in the process of carcinogenesis are conflicting and often lack conclusive evidence of causality. This underscores the need for further comprehensive research to elucidate the intricate relationship between this parasitic infection and the development of hepatic disorders ( 92 ).…”
Section: Resultsmentioning
confidence: 99%
“…Artemisinin (12, Figure 3) and its congeners are the active ingredients in the extracts of Artemisia annua, which have been used as traditional Chinese medicine for a variety Oxamniquine (OXA) and related compounds (6)(7)(8)(9)(10)(11).…”
Section: Antischistosomal Antimalarials 41 Artemisininsmentioning
confidence: 99%
“…Chronic schistosomiasis is associated with diseases of the kidneys, spleen, liver, bladder and intestine [3]. In endemic areas, up to 75% of the incidence of bladder cancer has been attributed to infection with S. haematobium; [4,5] the link between S. mansoni infection and cancer is still being investigated [6]. In all, the global burden due to schistosomiasis, in terms of disability-adjusted life years (DALYs, which combine premature mortality data with years lived with a disability) has been estimated at 1.7-4.5 million [7].…”
Section: Introductionmentioning
confidence: 99%
“…The studies have shown that it is closely related to schistosomal infection [1,2] . Human schistosomiasis manifests in three main types: S.haematobium S.mansoni and S.japonicum [3,4] , mainly schistosomiasis japonica in China. It is a parasitic disease widely prevalent along the Yangtze River Basin.…”
Section: Introductionmentioning
confidence: 99%